Nonparametric tests of collectively rational consumption behavior: An integer programming procedure. - Cherchye, Laurens; Rock, Bram De; Sabbe, Jeroen; Vermeulen, Frederic (Journal of Econometrics, 2008)
We present an IP-based nonparametric (revealed preference) testing procedure for rational consumption behavior in terms of a general collective model, which includes consumption externalities and public consumption. An empirical application to data drawn from the Russia Longitudinal Monitoring Survey (RLMS) demonstrates the practical usefulness of the procedure. Finally, we present extensions of the testing procedure to evaluate the goodness-of-fit (accounting for optimization error as well as measurement error) of the collective model subject to testing. Copyright (c) 2008 Elsevier B.V.